Re-Introducing Indonesian Traditional Games through an Interactive Multiplayer Table Game - Gobak Sodor - Emanuel Pratalaharja; Bayu Dirgantoro (Bina Nusantara University, 2021)
Nowadays, many people have left their country’s traditions and cultures due to advancement of technologies. Indonesia is rich in diversity, also its traditional games that are an inseparable part of Indonesian culture that should be preserved. Traditional games are almost unknown and abandoned as children lack early knowledge because parents and teachers disregard their important role in teaching these games to children. Traditional games are not up- to-date and are replaced by modern and digital games. Moreover, children nowadays have less free time and are physically less active. Additionally, there are less fields to play nowadays. This project aims to re-introduce Indonesian traditional games by creating an interactive multiplayer table game about Gobak Sodor for Indonesian children from Generation Z, especially those around 9-12 years old. It also aims to overcome misconceptions that traditional games are not fun and increase interest on traditional games. The research methodology was done through literature studies, qualitative methods including site visits and in-depth interviews. Overall, the game can be a fun playing experience that can be played in limited space and time to re-introduce traditional games to children and encourage them to preserve Indonesian culture.